SUBRETINAL CELL-BASED THERAPY: An Analysis of Surgical Variables to Increase Cell Survival. Issue 11 (November 2017) - Wilson, David J.; Neuringer, Martha; Stoddard, Jonathan; Renner, Lauren M.; Bailey, Steven; Lauer, Andreas; McGill, Trevor J.
Abstract : Purpose: To develop a novel surgical approach to provide consistent delivery of cell suspension into the subretinal space without cell leakage into the vitreous. Methods: Cell viability was assessed following mock injections to determine the optimal size cannula for delivery of the cells. A pars plana without vitrectomy approach was used to create a subretinal bleb with balanced salt solution using a 41-gauge cannula. GFP-labeled retinal pigment epithelium cells were injected through transretinal (n = 8) and transscleral (n = 16) injection approaches. Optical coherence tomography, fundus photography and autofluorescence, and histological analysis were used to evaluate surgical success. Results: The 30-gauge cannula yielded the highest recovery of cells with highest viability. The transretinal approach consistently resulted in transplanted cells in the vitreous, with some cells coming to rest on the inner limiting membrane. Conversely, the transscleral approach resulted in transplantation of cells into the subretinal space in 100% of cases. Histological analysis confirmed these results. Conclusion: We have developed a novel surgical approach that resulted in encapsulation of transplanted cells into the subretinal space with a 100% success rate. This approach will provide a useful tool for further cell transplantation study and may provide an approach for clinical application of delivering cells to the subretinal space. Abstract : Supplemental Digital Content is Available in the Text.The authors developed a novel transscleral surgical approach for delivery of cell suspension into the subretinal space of nonhuman primates that was successful in all cases. Use of this approach may be appropriate for clinical application of cell-based therapy.